Influence of Sanitizers on the Lipopolysaccharide Toxicity of Escherichia coli Strains Cultivated in the Presence of Zygosaccharomyces bailii. (25th May 2014) - Mogotsi, Lerato; De Smidt, Olga; Venter, Pierre; Groenewald, Willem
Abstract : The influence of sublethal concentrations of two sanitizers, liquid iodophor and liquid hypochlorite (LH), on the growth rates and toxicity of food-borne pathogenic Escherichia coli strains grown in the presence of spoilage yeast Zygosaccharomyces bailii was assessed. When grown in combination with Z. bailii both E. coli O113 and E. coli O26 exhibited slower growth rates, except when E. coli O113 was grown in combination with Z. bailii at 0.2% LH. The growth rate of Z. bailii was not impacted by the addition of the sanitizers or by communal growth with E. coli strains. LAL and IL-6 results indicated a decrease in toxicity of pure E. coli cultures with comparable profiles for control and sanitizer exposed samples, although the LAL assay proved to be more sensitive. Interestingly, pure cultures of Z. bailii showed increased toxicity measured by LAL and decreased toxicity measured by IL-6. LAL analysis showed a decrease in toxicity of both E. coli strains grown in combination with Z. bailii, while IL-6 analysis of the mixed cultures showed an increase in toxicity. The use of LAL for toxicity determination in a mixed culture overlooks the contribution made by spoilage yeast, thus demonstrating the importance of using the appropriate method for toxicity testing in mixed microbe environments.